Clinical Efficacy and Quality of Life Follow-Up of Reconstructive Endovascular Therapy for Acute Intracranial Vertebral Artery Dissection Aneurysms - Gao, Lu; Qian, Yu; Luo, Jing; Hong, Yang; Hu, Yangchun; Cheng, Hongwei; Cheng, Baochun (Frontiers in Surgery, 2020)
Background: Intracranial vertebral artery dissection aneurysms (VADAs) may cause acute ischemia or hemorrhage and the urgent endovascular treatment is needed. Although the majority of patients obtained a good functional outcome after surgery, the surprising finding was a bad quality of life (QOL) in the follow-up. The purpose of this study was to evaluate clinical efficacy and to analyze contributing factors of QOL after reconstructive endovascular therapy for acute intracranial VADAs. Methods: In this prospective study, 33 consecutive VADAs patients with subarachnoid hemorrhage were recruited in comparison to 37 VADAs patients with posterior circulation cerebral ischemia. All VADAs patients were treated using reconstructive strategy. The clinical, radiological, neurological and cognitive data, as well as QOL was performed at admission and six months after surgery. Stoke Specific Quality of Life (SS-QOL) was done for patients with good functional outcome (modified Ranking Scale (mRS) scoring 0-2) for subgroup analysis. Predictors for QOL at follow-up were analyzed by regression model. Results: Immediate angiography after surgery showed 57 (81.4%) patients were complete obliteration and 13 (18.6%) patients were partial obliteration in VADAs. Three (4.3%) cases suffered from perioperative complications, which contained 2 cases of stent thrombosis in hemorrhagic group and 1 case of posterior inferior cerebellar artery occlusion in ischemic group. Of 25 (75.8%) patients in hemorrhagic group and 30 (81.1%) patients in ischemic group had a favorable outcome (mRS scoring 0-2) in 6 months follow-up. Follow-up angiography displayed that 1 case of recurrence occurred separately in both group. 15 of 33 hemorrhagic patients (45.5%) and 19 of 37 ischemic patients (51.4%) rated QOL at follow-up as bad (SS-QOL score ≤ 3.9) despite of good function outcome. Severity of neurological disorder and impaired neurocognition at baseline in VADAs patients are proved to be independent predictors for decline of QOL according to regression analysis. Conclusion: Reconstructive endovascular therapy for acute intracranial VADAs is a safe and effective method with a low complication rate. VADAs lead to impaired QOL at 6 months follow-up attributed to multiple factors. The study demonstrated that neurological and cognitive status at baseline of significant importance for the QOL after VADAs.